Educational speech therapy and autism: lags and losses of the remote teaching modality in the midst of the COVID-19 pandemic (2020 to 2021) (Research, Society and Development, 2021)
The educational speech therapy professional is responsible for providing support to parents and teachers, especially with regard to the impairment of speech and language in the teaching-learning process. The objective of this research was to analyze the delays and losses of the remote teaching modality amid the COVID-19 pandemic of people with Autistic Spectrum Disorder (ASD) for this, an Integrative Review (IR) was carried out following what Cooper proposes (1984) based on the literature produced in the Scientific Electronic Library Online (SciElo), the searches resulted in 11 researches, comprised in the biennium (2020 and 2021). The results highlight the largest number of researches related to Assistive Technology (AT), which has an interdisciplinary characteristic, encompassing resources, methodologies, strategies, among others. Another aspect pointed out in the researches was the difficulties in communication and social interaction imposed by remote education and social isolation, which made the processes of school and digital inclusion difficult. The family, the school and the guidance of health professionals formed the tripod. Which suppressed communication, verbalization and oral language barriers caused by social isolation and low interaction of this public.